(untitled) (Research, Society and Development, 2022)
Would it be possible to identify in our contemporary actions traces that link with broader historical processes that are still ongoing? As much as we consider the specificity of our contemporary experiences, it is impossible not to recognize worrying coincidences that link us to human types evaluated by the critique of the reflective look of certain philosophical traditions, here circumscribed to Nietzschean philosophy. The purpose of this article is to use the analysis of some passages in Nietzsche to help us in the task of unveiling the meaning of the puerile contemporary way of life, accustomed to a narrow doctrine of happiness and virtue that standardize their actions and remove their possibilities of developing a own direction according to the requirements of its singularities. Nietzsche called his contemporaries the “last men”, those who, according to Zarathustra, “do not know what love is, what creation is, what longing is, but they say they invented happiness”, or those who “reduced labor to a pastime, they have given up what is painful, they have gained security and comfort, they consider that everyone is equal and they live for small pleasures”. What paths does Nietzsche take to compose his judgment and present this debased human type? We will use two recent facts, completely distant in their geographical location and in their political dimension, that occurred in the years 2021-2022, to illustrate our similar contemporary condition of diminution: what the play of a group of children can be related to the outcome of the French presidential elections?